A Comparative Performance Evaluation of 2D Nanomaterials for Applications in Plasmonic Biosensing. Issue 17 (2nd August 2020) - Kang, Lixing; Das, Chandreyee Manas; Liu, Dan; Chen, Ming Wei; Coquet, Philippe; Hong, Guo; Yong, Ken-Tye
Abstract : Plasmonic sensing relies on the interaction between the electromagnetic light wave and free electrons that reside at the interface of two materials, one of them being a metal. Surface plasmon resonance (SPR)‐based biosensing has distinct advantages of providing real‐time and label‐free detection technique that is capable of giving accurate and repeatable results. 2D nanomaterials (graphene and transition metal dichalcogenides [TMDCs] such as MoS2 and WS2 ) have recently gained high popularity in the field of biomedical sciences. Using Biacore commercial SPR machine manufactured by GE Healthcare, the efficacy of various combinations of these materials coated on the plasmonic metal gold (Au) (Au + MoS2, Au + WS2, Au + graphene, Au + graphene + MoS2, and Au + graphene + WS2 ) is evaluated, in enhancing the sensitivity of the biosensor as compared with the standard Kretschmann configuration (only Au). Some simulation results are also presented at incident light wavelengths of 633 and 785 nm that are based on the angular interrogation method. To conclude, it is found that the sensitivity in the increasing order is: only Au < Au + MoS2 < Au + WS2 ≈ Au + graphene < Au + graphene + MoS2 < Au + graphene + WS2 . Abstract : 2D materials are being exclusively used for plasmonic biosensing due to their outstanding optical features. However, not all such materials are created equal and they differ in their plasmonic sensing capabilities. Thus, using commercial Biacore T200 SPR sensor, the efficiency of some common monolayer and heterolayered 2D materials prepared using graphene, MoS2, and WS2 is evaluated and compared.